1997
DOI: 10.1136/emj.14.1.16
|View full text |Cite
|
Sign up to set email alerts
|

A national census of those attending UK accident and emergency departments with asthma. The UK National Asthma Task Force.

Abstract: Objective-To obtain a representative national picture of the type of people with asthma attending accident and emergency (A&E) departments in the UK, the reasons why they attend, and to determine the proportion admitted to hospital. Design-A national census involving questionnaires. Setting-100 A&E departments throughout the UK. Subjects-All those with asthma attending because of asthma during a one week period in September 1994. Results-Details were obtained about 1292 attendances. About half of all attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
1
13
1
1
Order By: Relevance
“…A study that aimed to obtain a representative national picture of the type of people with asthma attending accident and emergency departments in the UK found that 425 (32.9%) of the attendees had been admitted in the previous 12 months and 316 (24.5%) had attended the emergency department in the previous 3 months [18]. Similarly, in a French multicentre trial of individuals with asthma attending emergency departments, 975 (26%) out of 3,772 patients were considered to have lifethreatening asthma, 340 (37%) had been hospitalised in the previous year and 75 (8%) had been previously ventilated [19].…”
Section: Patients With Severe Asthma Have Increased Rates Of Unschedumentioning
confidence: 99%
“…A study that aimed to obtain a representative national picture of the type of people with asthma attending accident and emergency departments in the UK found that 425 (32.9%) of the attendees had been admitted in the previous 12 months and 316 (24.5%) had attended the emergency department in the previous 3 months [18]. Similarly, in a French multicentre trial of individuals with asthma attending emergency departments, 975 (26%) out of 3,772 patients were considered to have lifethreatening asthma, 340 (37%) had been hospitalised in the previous year and 75 (8%) had been previously ventilated [19].…”
Section: Patients With Severe Asthma Have Increased Rates Of Unschedumentioning
confidence: 99%
“…In Ireland and the UK, adults seen in emergency settings are more likely to be unemployed 1,2 and to receive social assistance. 1 US and Irish studies 3,4 have found that ED patients are more likely to be male and single.…”
Section: Introductionmentioning
confidence: 99%
“…28 Other studies have found similar results, implying that there is a 'window of opportunity' to initiate treatment to prevent progression to a severe exacerbation. 29 Unfortunately, most patients lack action plans and an effective way of improving uptake of selfmonitoring remains elusive. 25,30,31 New technologies, such as smartphone and tablet computer apps could be used to address these issues, but the evidence for effectiveness remains unclear.…”
Section: Recognizing Deterioration In Symptomsmentioning
confidence: 99%